Fundamentals of materials for energy and environmental sustainability - Ginley, D. S. (David S.); Kahen, David (Cambridge University Press, 2012)
"How will we meet rising energy demands? What are our options? Are there viable long-term solutions for the future? Learn the fundamental physical, chemical and materials science at the heart of: [bullet] Renewable/non-renewable energy sources [bullet] Future transportation systems [bullet] Energy efficiency [bullet] Energy storage Whether you are a student taking an energy course or a newcomer to the field, this book will help you understand critical relationships between the environment, energy and sustainability. Leading experts provide comprehensive coverage of each topic, bringing together diverse subject matter by integrating theory with engaging insights. Each chapter includes helpful features to aid understanding, including a historical overview to provide context, suggested further reading and questions for discussion. Every subject is beautifully illustrated and brought to life with full color images and color-coded sections for easy browsing, making this a complete educational package. Fundamentals of Materials for Energy and Environmental Sustainability will enable today's scientists and educate future generations"--